The Role and Predictive Value of Cytokines in Atherosclerosis and Coronary Artery Disease - Tousoulis, Dimitris; K. Economou, Evangelos; Oikonomou, Evangelos; Papageorgiou, Nikolaos; Siasos, Gerasimos; Latsios, George; Kokkou, Eleni; Mourouzis, Kostantinos; Papaioannou, Spyridon; Deftereos, Spyridon; W. Cleman, Michael; Lymberi, Maria; et al. (Current Medicinal Chemistry, 2015)
Atherosclerosis is currently regarded as a chronic inflammatory disease that is mediated by several types of cells and molecules. Emphasis has been placed on the role of cytokines and the way they act and interact to initiate and sustain inflammation in the microenvironment of an atherosclerotic plaque. Cytokines are invariably expressed by all cells involved in the pathogenesis of atherosclerosis, act on a variety of targets exerting multiple effects and are largely responsible for the crosstalk among endothelial, smooth muscle cells, leukocytes and other vascular residing cells. In the present paper our aim is to review current information on the role of the most commonly discussed cytokines in the process of atherogenesis and to discuss the prognostic significance of these cytokines in atherosclerosis and coronary artery disease.
Keywords: coronary artery disease